Efeitos da prolina exógena e sistema de ventilação natural no crescimento in vitro de orquídeas - da Silva, Adriano Bortolotti; dos Reis, Caroline Oliveira; Cazetta, Jairo Osvaldo [UNESP]; Carlin, Samira Domingues; Landgraf, Paulo Roberto Corrêa; dos Reis, Marinacunha (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2016)
Micropropagation is an alternative to produce orchid plants in large scale. However, this process presents losses during acclimatization. Exogenous proline use in vitro plant tissue culture can reduce the stress of the plant acclimatization phase. We aimed to verify the growth of orchids in different micropropagation systems with the addition of proline in the culture medium. Cattleya walkeriana plants were obtained from the germination of seeds in culture medium. Seeds were germinated in MS medium, added 20 g. L-1 of sucrose, solidified with 6 g. L-1 of agar and pH adjusted for 5,8. The cultures were incubated in a growth room with temperature of 24 ± 2 0C, under photoperiod of 16 h. After 5 months, 1-cm long seedlings were placed in a culture vessel according to the treatments, which were composed of two micropropagation systems (conventional and natural ventilation) and three proline concentrations (0, 1, and 2 g·L-1). The experiment was carried out in an entirely randomized design consisting of a 2 × 3 factorial, for a total of 6 treatments, each with 5 replicates. The natural ventilation system with the use of proline (1 g·L-1) promoted higher dry mass accumulation and better control of water loss by plants.
Effects of exogenous proline and a natural ventilation system on the in vitro growth of orchids
Keywords: Abiotic stress; Cattleya walkeriana; Micropropagation